Effects of antibiotics on the in vitro expression of tetracycline-off constructs and the performance of Drosophila suzukii female-killing strains - Yan, Ying; Hosseini, Bashir; Scheld, Annemarie; Pasham, Srilakshmi; Rehling, Tanja; Schetelig, Marc F. (Frontiers in Bioengineering and Biotechnology, 2023)
Genetic control strategies such as the Release of Insects carrying a Dominant Lethal (RIDL) and Transgenic Embryonic Sexing Systems (TESS) have been demonstrated in the lab and/or deployed in the field. These strategies are based on Tetracycline-off (Tet-off) systems which are regulated by antibiotics such as Tet and doxycycline (Dox). Here we generated several Tet-off constructs carrying a reporter gene cassette mediated by a 2A peptide. Different concentrations (0.1, 10, 100, 500, 1000 µg/mL) and types (Tet or Dox) of antibiotics were used to evaluate their effects on the expression of the Tet-off constructs in the Drosophila S2 cells. One or both of the two concentrations, 100 and 250 µg/mL, of Tet or Dox were used to check the influence on the performances of a Drosophila suzukii wildtype strain as well as female-killing (FK) strains employing TESS. Specifically, the Tet-off construct for these FK strains contains a D. suzukii nullo promoter to regulate the tetracycline transactivator and a sex-specifically spliced pro-apoptotic gene hidAla4 to eliminate females. The results suggested that the in vitro expression of the Tet-off constructs was controlled by antibiotics in a dose-dependent manner. ELISA experiments were carried out identifying Tet at 34.8 ng/g in adult females that fed on food supplemented with Tet at 100 µg/mL. However, such method didn’t detect Tet in the eggs produced by antibiotics-treated flies. Additionally, feeding Tet to the parents showed negative impact on the fly development, but not the survival in the next generation. Importantly, we demonstrated that under certain antibiotics treatments females could survive in the FK strains with different transgene activities. For the strain V229_M4f1 which showed moderate transgene activity, feeding Dox to fathers or mothers suppressed the female lethality in the next generation, and feeding Tet or Dox to mothers generated long-lived female survivors. For the strain V229_M8f2 which showed weak transgene activity, feeding Tet to mothers delayed the female lethality for one generation. Therefore, for genetic control strategies employing the Tet-off system, the parental and transgenerational effects of antibiotics on the engineered lethality and insect fitness must be carefully evaluated for a safe and efficient control program.